2014
DOI: 10.1007/s00592-014-0643-6
|View full text |Cite
|
Sign up to set email alerts
|

The use of continuous glucose monitoring systems in a pediatric population with type 1 diabetes mellitus in real-life settings: the AWeSoMe Study Group experience

Abstract: The adoption of RT-CGMS was low, even in a healthcare system that funds its use. Caregivers should consider patient characteristics when recommending RT-CGMS use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 18 publications
1
36
0
Order By: Relevance
“…Specifically, at 3 months, 71 youths (86%) were using CGM at least 75% of the time while at 12 months, only 32 youths were using CGM at least 75% of the time. 41 These data suggest that other patient characteristics may have a greater influence on CGM use than cost. For example, although not specifically predictive of frequency of use, other studies have found relations between better outcomes using CGM and patient-report of greater motivation for glycemic control, better coping resources, a better understanding of how to use CGM data, and greater family support, suggesting the opposites of all of these could be additional barriers to use.…”
Section: Real-time Cgmmentioning
confidence: 93%
See 1 more Smart Citation
“…Specifically, at 3 months, 71 youths (86%) were using CGM at least 75% of the time while at 12 months, only 32 youths were using CGM at least 75% of the time. 41 These data suggest that other patient characteristics may have a greater influence on CGM use than cost. For example, although not specifically predictive of frequency of use, other studies have found relations between better outcomes using CGM and patient-report of greater motivation for glycemic control, better coping resources, a better understanding of how to use CGM data, and greater family support, suggesting the opposites of all of these could be additional barriers to use.…”
Section: Real-time Cgmmentioning
confidence: 93%
“…10,11 Cost of CGM supplies has also been identified as a barrier to use. 11,41 Indeed, cost may be a formidable barrier in countries with limited insurance reimbursement for CGM. However, a recent study tested the impact of cost on CGM frequency of use in Israel, where CGM is covered by their national health insurance program.…”
Section: Real-time Cgmmentioning
confidence: 99%
“…The costs of devices were prohibitive as well and were not well covered by national or private insurance plans. Even when the costs of the devices are covered, 57 % of patients at 12 months no longer used sensors [4]. Consistent users tended to be younger with more frequent baseline meter glucose measurements.…”
Section: Continuous Glucose Monitoring Systemsmentioning
confidence: 93%
“…The authors conclude that providers should be aware that CGM is most useful in compliant patients. 51 Naranjo et al reported in 2016 that those using pumps, CGMs, or sensor augmented pumps had more positive attitudes about diabetes technology than those on multiple daily injections and conventional glucose monitoring. 52 Among all participants in the JDRF CGM study group common barriers to continued use include insertion pain, system alarms, and body issues related to the need to wear the device, 53 although this was with early generation systems.…”
Section: Special Considerations In Pediatricsmentioning
confidence: 99%